Halk dilinde bir duâ mecmûası: Bilâl nûrî münâcâtı - (:unkn) unknown (My University, 2012)
Eski Türk edebiyatı ürünlerinden olan münâcât, ibâdet/duâ ile edebiyâtın kesiştiği noktadadır. Bu sebeple münâcâtlar, bazı duâ mecmûalarına da girmiştir. İbâdeti edebiyat ile süsleyen bu tür neşirlere halkın ziyâdesiyle rağbet gösterdiği anlaşılmaktadır. Bu makalenin konusu, bu türün tipik örneklerinden olan ve XIX. asrın sonlarında yayımlanan Bilal Nûri Münâcâtıdır. Söz konusu kitapçık ayrıntılı şekilde tanıtıldıktan sonra şekil ve muhtevâ bakımından incelenmiş, ayrıca metnin tamamı transkripsiyon alfabesine aktarılmıştır.

As a product of Old Turkish Literature, munādjāt is common for prayers and literature. So munādjāts are recorded to the some collections of prayers. It can be undersood obviously that people admired these publications which adorn prayers with literature to a great degree. The subjet of this paper is Munādjāt of Bilal Nūri one of the typical pieces of this genre, printed in the XIXth century. In this paper, particular information about this booklet will be given, the text will be reviewed as form and content. In addition, all of the text will be written in transcription.
A prayer treatise for the public: Munādjāt of bilal nūri
Keywords: Kültürel Çalışmalar; Folklor; Edebiyat